Análisis sociológico del impacto de las políticas públicas orientadas a la inclusión social de integrantes de grupos LGBTI, 2007- 2019 - Ludeña Reyes, Manuela Alejandra (My University, 2020)
The improvements in public policies in Ecuador have allowed the inclusion of LGBTI collective groups during the last 12 years 2007-2019, this is due to the repeated various forms of unprecedented violations of the rights of these groups such as crimes, illegal arrests, bullying, physical and verbal aggressions, and other acts of homophobia. The Constitutional Referendum of Ecuador of 2008 convened by the government of the Eco. Rafael Correa Delgado, allowed the approval of a new constitution created in the National Constituent Assembly of 2007, and with it, the transition to a new era of rights claims and, to the establishment of mechanisms of social inclusion in public policies. The political and social participation of LGBTI group became increasingly visible and strong in the elections, in public - private functions and in the event of gay pride. Therefore, the need to include the community within a conservative society through public policies became increasingly strong. In the year 2019, the decision of the constitutional court to sentence in favor of equal marriage, took another step towards respecting the rights of LGBTIs. The approval of marriage for all is the confirmation of a government that is committed to guarantee equality, however, if the law changes, this does not mean that the mentalities and the practices should keep following the same path, there is still much work to be done to ensure that this new mentality, the inclusion in all its forms is present in all spheres of the government and the society.
Las mejoras de las políticas públicas en Ecuador han permitido la inclusión de los colectivos LGBTI durante los 12 últimos años 2007-2019, debido a las reiteradas variadas formas de violaciones sin precedentes a los derechos de estos grupos crímenes, arrestos ilegales, bullying, agresiones físicas y verbales, y demás actos de homofobia. El Referéndum Constitucional de Ecuador de 2008 convocado por el gobierno del Eco. Rafael Correa Delgado, posibilitó la aprobación de una nueva constitución gestada en la Asamblea Nacional Constituyente de 2007, y con ello, el paso a una nueva era de reivindicación de derechos y, al establecimiento de mecanismos de inclusión social en las políticas públicas. La participación política y social de los lgbtistas se hicieron cada vez más visibles y fuertes en las elecciones, en las funciones públicas - privadas y en el evento del orgullo gay. Por ello, la necesidad de incluir a la comunidad dentro de una sociedad conservadora mediante políticas públicas se volvió cada vez más fuerte. En el año 2019, la decisión de la corte constitucional de sentenciar a favor el matrimonio igualitario, dio un paso más hacia el respeto de los derechos de los LGBTI. La aprobación del matrimonio para todos, es la confirmación de un gobierno que se compromete a garantizar la igualdad, sin embargo, si la ley cambia no quiere decir que las mentalidades y las practicas sigan el mismo camino, todavía queda mucho trabajo por hacer para garantizar que esté presente en todas las esferas del gobierno y la sociedad.
Keywords: ANALISIS SOCIOLOGICO; POLITICA PUBLICA; INCLUSION SOCIAL; LGTBI